STARTUP AS A DIPLOMA MASTER'S PROJECT: FROM THE IDEA TO A PRACTICAL IMPLEMENTATION - Netreba Margaryta (Borys Grinchenko Kyiv Metropolitan University, 2020)
The article deals with the new principle of diploma defence (protection) for Ukrainian higher education in the form of start-ups on the example of the masters of educational and professional program «Advertising and Public Relations» Borys Grinchenko Kyiv University, which provides great opportunities for the establishment of innovative environment and every alumnus confirms very high level of qualification which was acquired during years of university study. The possible results of such a step for the development of entrepreneurship in Ukraine are also being evaluated. On the grounds of content analysis, the theme of master's thesis of professional program «Advertising and Public Relations are analyzed as a result of willingness to solve difficult tasks and problems in professional activity, competence to apply the acquired knowledge in applied scientific research, practical communication projects, in public, commercial, creative and other socially beneficial activities with the help of future specialists in the field of advertising and PR. The structural components of a master's startup project are described in the details, as well as an evaluation criteria and a range of possible points for their implementation were pointed out. clearly defined criteria for evaluating startup projects: creativity, visual effects, aesthetic impression, originality, style, composition, etc. The conclusions which are relative to the dynamic of development such masters' startups are formulated in the form of more complicated, integrated interdisciplinary project, in which individual parts can be performed by a master of another structural subdivision(unit) of Borys Grinchenko Kyiv University or even other higher education institution.